2015
DOI: 10.1038/srep09925
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple myeloma acquires resistance to EGFR inhibitor via induction of pentose phosphate pathway

Abstract: Multiple myeloma (MM) was characterized by frequent mutations in KRAS/NRAS/BRAF within the EGFR pathway that could induce resistance to EGFR inhibitors. We here report that EGFR inhibition solely exhibited moderate inhibition in KRAS/NRAS/BRAF wildtype (triple-WT) MM cells, whilst had no effect in myeloma cells with any of the mutated genes. The moderate inhibitory effect was conferred by induction of pentose phosphate pathway (PPP) when cells were treated with Gefitinib, the EGFR inhibitor. Combination of Gef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…We showed that OCR, an indicator of oxidative phosphorylation, was suppressed following METi in METi-sensitive M1268T cells. This observation is in line with previously reported modulations of cellular metabolism by EGFR signaling, where Makinoshima et al documented changes in OCR in EGFR-inhibitor-treated lung adenocarcinoma cell line HCC827 and similar result was recapitulated by Chen et al in myeloma cells treated with the specific EGFR inhibitor gefitinib [38,39]. The OCR drop in M1268T cells might be caused by impairment of mitochondrial function via mitochondrial membrane depolarization following tepotinib administration, which was previously reported using other tyrosine kinase inhibitors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We showed that OCR, an indicator of oxidative phosphorylation, was suppressed following METi in METi-sensitive M1268T cells. This observation is in line with previously reported modulations of cellular metabolism by EGFR signaling, where Makinoshima et al documented changes in OCR in EGFR-inhibitor-treated lung adenocarcinoma cell line HCC827 and similar result was recapitulated by Chen et al in myeloma cells treated with the specific EGFR inhibitor gefitinib [38,39]. The OCR drop in M1268T cells might be caused by impairment of mitochondrial function via mitochondrial membrane depolarization following tepotinib administration, which was previously reported using other tyrosine kinase inhibitors.…”
Section: Discussionsupporting
confidence: 90%
“…documented changes in OCR in EGFR‐inhibitor‐treated lung adenocarcinoma cell line HCC827 and similar result was recapitulated by Chen et al . in myeloma cells treated with the specific EGFR inhibitor gefitinib . The OCR drop in M1268T cells might be caused by impairment of mitochondrial function via mitochondrial membrane depolarization following tepotinib administration, which was previously reported using other tyrosine kinase inhibitors.…”
Section: Discussionsupporting
confidence: 51%
“…Changes in the PPP activity can affect response to anticancer drugs, however the specific role of PPP in MDR phenotype is still unclear. Other authors implied that PPP is more active in MDR tumors2728. Moreover, evidence suggested that elevated levels of NADPH and GSH, together with an active PPP, play an important role in MDR2930.…”
Section: Discussionmentioning
confidence: 99%
“…In the nonoxidative phase, the pentose phosphates produced during the oxidative phase are recycled into glucose 6-phosphate. By providing cells with ribonucleotides for nucleic acid synthesis, and NADPH for lipid synthesis and redox homeostasis, PPP plays a critical role in cancer cell metabolism and often become activated in various cancers including solid tumors [8], AML [22], multiple myeloma [23], and lymphoid leukemias [24]. Inhibition of PPP in cancer cell lines reduces NADPH levels, lipid synthesis, and also reprograms metabolism by increasing oxidative phosphorylation [22] or glycolysis.…”
Section: Increased Glucose Metabolism Supports Anabolism and Redoxmentioning
confidence: 99%